Spontaneous breathing trial with low pressure support protocol for weaning respirator in surgical ICU - Kaweesak Chittawatanarat (2018)
Objective: Compare the effectiveness between spontaneous breathing trial with low-pressure support protocol and liberal or non-protocol directed method. Material and Method: The authors conducted a retrospective study involving 577 patients who were arranged and appropriate to weaning from mechanical ventilation on general surgical intensive care unit between July 1, 2004 to June 30, 2007. Two hundred and twenty two patients were weaned by their host surgeons or team (liberal group). Three hundred and fifty five patients underwent once daily spontaneous breathing trial with low-pressure support protocol. Patients assigned to this protocol had the pressure support level decreased to 5-7 cm of water for up to two hours each day. If signs of intolerance occurred, the process was restrained while patients who tolerated the two-hour trial without signs of distress were extubated. The authors collected demographic data, cause of ICU admission, APACHE II score at arranged time to weaning, weaning process time, ventilator day, and ICU length of stay. Results: There was statistical difference between liberal and protocol in age (59.2 ± 19.3 vs. 55.6 ± 19.8; p = 0.03) but there was no statistical difference in gender (male 74.3 vs. 67.9%; p = 0.2) and APACHE II score at arranged time to wean (14.7 ± 7.4 vs. 15.3 ± 6.3; p = 0.2). The median (inter-quartile) range duration of weaning process (29.5 (48) vs. 2.25 (2.9), p < 0.001), ventilator day (3 (4) vs. 2 (3), p < 0.001), and length of ICU stay (5 (5) vs. 3 (3), p < 0.001) were shorter in the protocol group than the liberal group. Multivariate linear regression model also revealed significantly less duration of weaning process in the protocol group than the liberal group in terms of weaning time (-63.6 (-74.7 to -2.6) hours), ventilator day (-3.0 (-3.7 to -2.2) days), and length of ICU stay (-2.9 days (-3.7 to -2.0); p < 0.001) (95% confidence interval). Conclusion: Spontaneous breathing trial with low-pressure support protocol for liberal from mechanical ventilator was effective to reduce weaning time, ventilator day, and length of ICU stay in general surgical intensive care units.